2012
DOI: 10.1155/2012/397813
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide and Parylene Surface Coating of Polystyrene and ePTFE for Improved Endothelial Cell Attachment and Hemocompatibility

Abstract: In vivo self-endothelialization by endothelial cell adhesion on cardiovascular implants is highly desirable. DNA-oligonucleotides are an intriguing coating material with nonimmunogenic characteristics and the feasibility of easy and rapid chemical fabrication. The objective of this study was the creation of cell adhesive DNA-oligonucleotide coatings on vascular implant surfaces. DNA-oligonucleotides immobilized by adsorption on parylene (poly(monoaminomethyl-para-xylene)) coated polystyrene and ePTFE were resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…14 In addition, a study by Schleicher et al showed that PC exhibits low thrombogenicity and excellent hemocompatibility after oligonucleotide coating. 13 In the current study, we showed that cellular morphology, phenotype, and viability of PVECs and PVICs grown on plasma-treated PC showed similar patterns to cells grown in normal in vitro conditions.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…14 In addition, a study by Schleicher et al showed that PC exhibits low thrombogenicity and excellent hemocompatibility after oligonucleotide coating. 13 In the current study, we showed that cellular morphology, phenotype, and viability of PVECs and PVICs grown on plasma-treated PC showed similar patterns to cells grown in normal in vitro conditions.…”
Section: Discussionsupporting
confidence: 58%
“…The ability of the scaffold material to adsorb ECM proteins is important in providing such an environment. 13 In addition, surface wettability is an important factor in enhancing cell adhesion and protein adsorption. 23 In this study, we applied two surface modifications to PC: first, we plasma oxidized PC to induce its hydrophilicity, and then we coated the material with a range of concentrations of ECM proteins to provide a favorable environment for cellular adhesion and growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aptamer-coated polymeric surfaces were able to promote the selective adhesion of EPCs followed by their differentiation into endothelial cells after ten days. Similarly, in a more recent study, DNA oligonucleotides were immobilized on different vascular grafts made of expanded polytetrafluoroethylene (ePTFE) and polystyrene to promote in situ endothelialization [131]. The coated surfaces allowed adhesion of murine EPCs and showed low thrombogenicity and improved hemato-compatibility with human blood.…”
Section: Cardiovascular Regeneration Using Stem Cell Recruitment Smentioning
confidence: 99%
“…85 In a recent study, DNA-oligonucleotide coatings were immobilized by adsorption on parylenecoated ePTFE and polystyrene using vapor deposition. 86 Murine EPCs, HUVECs, and adult human ECs were seeded. Dynamic culture conditions were maintained to apply constant shear stress.…”
mentioning
confidence: 99%